Solve for q y=19-q

Math
y=19-q
Rewrite the equation as 19-q=y.
19-q=y
Subtract 19 from both sides of the equation.
-q=y-19
Multiply each term in -q=y-19 by -1
Tap for more steps…
Multiply each term in -q=y-19 by -1.
(-q)⋅-1=y⋅-1+(-19)⋅-1
Multiply (-q)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1q=y⋅-1+(-19)⋅-1
Multiply q by 1.
q=y⋅-1+(-19)⋅-1
q=y⋅-1+(-19)⋅-1
Simplify each term.
Tap for more steps…
Move -1 to the left of y.
q=-1⋅y+(-19)⋅-1
Rewrite -1y as -y.
q=-y+(-19)⋅-1
Multiply -19 by -1.
q=-y+19
q=-y+19
q=-y+19
Solve for q y=19-q

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top